Legal Strategies for Addressing the Environmental Challenges: A Pathway to Sustainable Governance in Pakistan - Shaikh, Shuhab Ud Din; Mangi, Rabel; Abro, Khuram (Pakistan Languages and Humanities Review, 2025)
The article examines the legal systems and sustainable governance practices Pakistan uses to handle environmental crises. The implementation of the Pakistan Environmental Protection Act of 1997 meets financial support requirements but suffers from inadequate institutional capabilities and weak enforcement ability thus diminishing its operational effectiveness. This research examines environmental law effectiveness in present times before proposing governance development strategies. Legal and policy documents serve as the basis for qualitative research conducted by authors who demonstrate that institutional capacity together with public involvement and standard adherence play central roles. The analysis shows emergency regulatory shortcomings that need advanced institutional systems and better public knowledge. The paper points out that environmental problems need customized legal treatment. Environmental sustainability and governance management in Pakistan needs development of three fundamental elements which include accountable systems alongside transparent operational procedures and institutional resilience for enduring administration.